THE TECHNOLOGY OF "ECOBRICK ROSTER" FROM PLASTIC WASTE IN MOSQUE BUILDING ORNAMENTS AS A RECYCLING SOLUTION - Nandaru Syamsahima; Ana Fitrotun Nisa’ Fitrotun Nisa’; Samsul Ma’arif; Adinda Septi Hendriani Septi Hendriani; Heri Hermanto (CATHA SAINTIFICA, 2024)
Plastic waste management is a growing global challenge, particularly in Indonesia, which produces 1,278,900 tons of plastic waste annually. Efforts to address this issue include processing plastic waste into valuable products such as rosters, which can serve as eco-friendly solutions. This study aims to develop technology for managing plastic waste into rosters, focusing on the use of sustainable recycled materials with economic value. Based on previous research demonstrating the successful use of plastic waste in the production of paving blocks, this study adopts a similar method for producing rosters. The methods employed in this research include analyzing plastic recycling technologies, designing innovative roster products, and testing the quality of the resulting products. The findings reveal that rosters made from plastic waste possess good quality, are environmentally friendly, and have the potential to become an innovative solution for waste management in Indonesia. Furthermore, the implementation of this technology contributes to reducing plastic waste, environmental pollution, and creating new economic opportunities through the recycling industry. Thus, utilizing plastic waste to produce rosters not only supports environmental preservation efforts but also provides social and economic benefits to communities. This study is expected to encourage broader use of eco-friendly technologies in the future and increase public awareness of the importance of sustainable waste management. .